ANALIZA ŞI EVALUAREA COERENŢEI SISTEMULUI DE OBIECTIVE DIN CADRUL CURRICULUMULUI ŞCOLAR PROIECTAT PRIN METODA HĂRŢII DE DEZVOLTARE OPERAŢIONALĂ A CONCEPTELOR - USM ADMIN (Moldova State University, 2007)
The operational concepts development map is an evaluation method of the educational curriculum coherence degree designed by the appreciation of the quality development regarding the disciplinary objectives system during an entire education cycle. This method emphasizes, in the shape of two entries table, all the important objectives of every school year and also their succession. The adequate degree examination analysis of the reference objectives to the main objective, from which they arise, enables eliminations, completions or even position changes of these objectives.